Stereotyped perceptions of chronic pain - Møller, Marie Østergaard (Tidsskrift for Forskning i Sygdom og Samfund - Journal of Research in Sickness and Society, 2010)
This essay is a reflection on my professional norms when I do pain research, treat pain patients, and communicate with the social system. Being both a medical doctor and a clinical researcher, I daily have to combine what I see as arbitrary rationalities in my approach to pain. The reason is that pain research is often conducted within a theoretical framework that mainly understands pain as a physical or biomedical phenomenon even though a broader and more precise perspective on pain exists - and is often used when physicians treat patients. It is of interest to see how easily doctors use different concepts of pain when they conduct biomedical research with advanced equipment and standardized tools with one hand, and with the other hand talk to patients, trying to focus on their needs and helping them cope with their pain using a very broad perceptive of pain. This dilemma of acting both as a researcher and a clinical doctor is not often discussed or reflected upon by doctors. An explanation could be the focus on productivity and efficiency that rules the everyday life of most doctors as opposed to a focus on reflection, concepts, and values in pain medicine. The focus of this essay is therefore to describe, reflect, and elaborate on the differences of pain as an object of research, treatment, and decision-making. In other words, to reflect upon the ambiguous practice doctors engage in when doing pain research and treating chronic pain patients. Furthermore, this essay may contribute to our understanding of why decisions on eligibility in the social system are made without adequate documentation of patients’ chronic pain conditions.